Secondary electron time detector for mass measurements at CSRe - 涂小林 王猛 胡正国 徐瑚珊 郭忠言 毛瑞士 肖国青 张宏斌 臧永东 岳珂 (Chinese physics C, 2010)
The Isochronous Mass Spectrometry is a high accurate mass spectrometer. A secondary electrons time detector has been developed and used for mass measurements. Secondary electrons from a thin carbon foil are accelerated by an electric field and deflected 180°by a magnetic field onto a micro-channel plate. The time detector has been tested with alpha particles and a time resolution of 197 ps （FWHM） was obtained in the laboratory. A mass resolution around 8×10^-6 for Am/m was achieved by using this time detector in a pilot mass measurement experiment.